Insurance Products as Protection for Debtors Due to Failure to Implement Performance in Business Agreements - Nanda Utama (Master of Law Program, Ekasakti University, 2024)
In business protection, there are instruments that are able to anticipate business losses if one party does not carry out what has been agreed. An instrument called insurance. Insurance products according to Article 246 of the Commercial Code (KUHD) are